Airborne virus transmission via respiratory droplets: Effects of droplet evaporation and sedimentation. (October 2021) - Rezaei, Majid; Netz, Roland R.
Abstract: Airborne transmission is considered as an important route for the spread of infectious diseases, such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and is primarily determined by the droplet sedimentation time, that is, the time droplets spend in air before reaching the ground. Evaporation increases the sedimentation time by reducing the droplet mass. In fact, small droplets can, depending on their solute content, almost completely evaporate during their descent to the ground and remain airborne as so-called droplet nuclei for a long time. Considering that viruses possibly remain infectious in aerosols for hours, droplet nuclei formation can substantially increase the infectious viral air load. Accordingly, the physical-chemical factors that control droplet evaporation and sedimentation times and play important roles in determining the infection risk from airborne respiratory droplets are reviewed in this article. Graphical abstract: Image 1 Highlights: The physical-chemical mechanisms that control the airborne transmission of virus-containing saliva droplets are reviewed. Simple and transparent equations are presented to approximate the droplet evaporation and sedimentation times. Water evaporation increases the mean time aerosols stay sedimenting in air. Small aerosols completely evaporate to droplet nuclei during their descent to the ground and stay airborne for a long time. Solute effects slow down the droplet evaporation by reducing the water vapor-pressure and by inducing a concentration gradient in the droplet.